Partisipasi Politik dan Keterlibatan Masyarakat Pada Pemilu: (Studi Kasus: Kecamatan Dlingo, Kabupaten Bantul) - Nur, Utami; Mohammad Sukarno; Hardiyanto (Talenta Publisher, 2023)
The The purpose of this study was to determine the political participation and community involvement of Dlinggo District in the 2020 Bantul Regency Regional Election. The method used in this study is qualitative with a case study approach in Dlingo District to see political participation. The source of data in the study is primary data, sourced from author interviews conducted with the Division of Socialization, Voter Education, community participation and human resources of the Bantul Regency KPU. Second, secondary data sourced from data documents related to the percentage of political participation and social media data of the Bantul Regency KPU. Data analysis using Computer Asigned Qualitative Data Software (CAQDS) Nvivo 12plus. Data visualization is presented in the form of crosstab analysis graphs and Words Cloud Analysi. The results showed that political participation in Dlingo Subdistrict which included social and economic status, situation, political affiliations of parents, political awareness, organizational experience, trust in the government through mass media socialization and informal discussions in general the value of participation went well because of the high enthusiasm of the residents there. However, factors that have a fairly high influence conclude that from the indicators that have been met, the indicators of political awareness, the situation of trust in the government, and the stimulant of participation through mass media socialization and informal discussions have a value that is more determinant than others. This can be seen in the enthusiasm of residents (engagement) in every socialization carried out by the KPU and through social media, then also data on the level of public trust in the leadership of regional heads which is also a strong foundation in participating in new regional head elections and towards changes in service quality.